2010
DOI: 10.5152/akd.2010.125
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase type 5 inhibitors in the treatment of pulmonary arterial hypertension

Abstract: The pathology of pulmonary arterial hypertension (PAH) is characterized by vascular vasoconstriction, smooth muscle cell proliferation, and thrombosis. Experimental studies have shown the beneficial effect of phosphodiesterase type 5 (PDE-5) inhibitors on pulmonary vascular remodeling and vasodilatation. Randomized clinical trials in monotherapy or combination therapy have been conducted in PAH with sildenafil and tadalafil which significantly improve clinical status, exercise capacity and hemodynamics of PAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…18,19 In addition, recent studies have shown that sildenafil has beneficial effects on fracture healing by enhancing bone formation in experimental animal models. [20][21][22] This effect may be related to the beneficial effects of PDE5 inhibitors on vasodilatation, 23,24 angiogenesis 25,26 and the NO/cGMP/PKG signalling pathway. 27 In previous studies, it has been shown that there is a positive correlation between reactive oxygen species (ROS) and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In addition, recent studies have shown that sildenafil has beneficial effects on fracture healing by enhancing bone formation in experimental animal models. [20][21][22] This effect may be related to the beneficial effects of PDE5 inhibitors on vasodilatation, 23,24 angiogenesis 25,26 and the NO/cGMP/PKG signalling pathway. 27 In previous studies, it has been shown that there is a positive correlation between reactive oxygen species (ROS) and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sildenafil, erektil disfonksiyon ve pulmoner hipertansiyon tedavisinde kullanılmaktadır 16 . Fosfodiesteraz inhibisyonu ile cAMP-cGMP yolunda düzenleyici etkisi, güçlü vazodilatatör ve hücre koruyucu özellikleri ile sitotoksisiteyi önlediği deneysel olarak gösterilmiştir.…”
Section: Discussionunclassified
“…2012; Levin and White, 2011; Maki et al . 2011; Kiliçkesmez and Küçükoğlu, 2010]. It has been advocated to start tadalafil coadministration in patients with 6MWD of less than 380 m, signs of right-sided heart failure, persistent functional class III or IV symptoms refractory to treatment with one medication, or those patients who did not respond to the first-line therapy [Chin and Rubin, 2008; Hoeper et al .…”
Section: Clinical Study Data Reviewmentioning
confidence: 99%